Three-body recombination in ultracold systems: Prediction of weakly-bound atomic trimer energies - Tomio, L. [UNESP]; Filho, V. S. [UNESP]; Yamashita, Marcelo Takeshi [UNESP]; Gammal, A.; Frederico, T. (My University, 2004)
The three-body recombination coefficient of an ultracold atomic system, together with the corresponding two-body scattering length a, allow us to predict the energy E 3 of the shallow trimer bound state, using a universal scaling function. The production of dimers in trapped Bose-Einstein condensates, from three-body recombination processes, in the regime of short magnetic pulses near a Feshbach resonance, is also studied in line with the experimental observation.